Review on the Synthesis of Pyrazine and Its Derivatives - ONG, KOK TONG; LIU, ZHI-QIANG; TAY, MENG GUAN (Borneo Journal of Resource Science and Technology, 2017)
Pyrazine is a kind of natural product which can be found in plants, animals, insects, marine organisms and microorganisms. The main function of pyrazine in living organisms is used as flavor of the raw foods. Pyrazine and its derivatives were also produced in industries mainly for fragrance, flavor and pharmaceutical applications. This review describes the historical development of pyrazine including the discovery and synthesis, to the recent synthetic approach of pyrazinium. In general, six synthetic approaches namely condensation reaction, ring closure, metal catalysis, green reaction, Maillard reaction and acid catalyst on N-substitution have been reviewed in this paper. The first five approaches are mainly aimed for the substitution at 2, 3, 5 and 6 positions in pyrazine ring, whereas the last approach is specifically for 1 and 4 positions in pyrazine. Keywords: Diazine, pyrazine, and Maillard reaction